Wrestling with the complexity of evaluation for organizations at the boundary of science, policy, and practice. Issue 5 (1st August 2018) - Pitt, R.; Wyborn, C.; Page, G.; Hutton, J.; Sawmy, M. Virah; Ryan, M.; Gallagher, L.
Abstract: Boundary organizations are situated between science, policy, and practice and have a goal of supporting communication and collaboration among these sectors. They have been promoted as a way to improve the effectiveness of conservation efforts by building stronger relationships between scientists, policy makers, industry, and practitioners (Cook et al. 2013). Although their promise has been discussed in theory, the work of and expectations for boundary organizations are less defined in practice. Biodiversity conservation is characterized by complexity, uncertainty, dissent, and tight budgets, so boundary organizations face the challenging task of demonstrating their value to diverse stakeholders. We examined the challenges boundary organizations face when seeking to evaluate their work and thus aimed to encourage more productive conversations about evaluation of boundary organizations and their projects. Although no off‐the‐shelf solution is available for a given boundary organization, we identified 4 principles that will support effective evaluation for boundary organizations: engage diverse stakeholders, support learning and reflection, assess contribution to change, and align evaluation with assumption and values. Abstract : Article impact statement : Appropriate evaluation for boundary organizations enhances their efforts to build relationships among conservation science, policy, and practice.